FAKTOR YANG MEMPENGARUHI KEJADIAN PNEUMONIA PADA BALITA DI PUSKESMAS KOTA PALEMBANG - Romadhon, Muhammad; Wulandari, Ria; Rimbawati, Yazika (NHM PRESS, 2024)
Lung parenchymal infection caused by exposure to various bacteria, viruses, parasites and infectious fungi is known as pneumonia. The death rate caused by pneumonia reaches 2,500 toddlers every day, or around two toddlers die every minute. UNICEF reported in 2015 that according to WHO, pneumonia causes 16% of deaths, while in Indonesia it is 14%. The aim of this research is to determine the factors associated with the incidence of pneumonia in toddlers. This quantitative research uses a cross-sectional approach. This study utilized all mothers with toddlers aged between 12 and 59 months who visited Public haelth X. A total of 86 respondents were taken by chance. This study used a question and answer sheet about pneumonia, family support, exclusive breastfeeding, and basic immunization status. Validity and reliability tests of the instruments used have been carried out. For analysis using the che square test was used. Data analysis shows that out of a total of 87 respondents who suffered from pneumonia, there were 15 respondents (16.3%) and 72 respondents (83.7%) who did not have pneumonia. And the Che Square test results obtained were the variable exposure to cigarette smoke with p value = 0.025 and OR 5.1, the variable history of exclusive breastfeeding with p value = 0.045 and OR 4.5, and the variable immunization status with p value = 0.000 and OR 3. 1 so it can be concluded that there is a relationship between exposure to cigarette smoke, exclusive breastfeeding and immunization status with the incidence of